FAKTOR YANG MEMPENGARUHI PEMEROLEHAN PARTIKEL LOKATIF NI DAN DE PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Suci Wahyu Ningsih; Nana Rahayu; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to explain what are the factors that influence the acquisition of locative particles ni and de in class 2019 students of the Japanese Language Education Study Program, FKIP Riau University. This study uses a qualitative descriptive approach. The sample in this study was Class 2019 students consisting of 3 (three) male students and 3 (three) female students. From the results of research using interviews, obtained several factors that affect the acquisition of locative particles ni and de such as motivation, formal study and environment.Keywords: Acquisition, Locative Particle, Motivation